Effects of apigenin, luteolin, and quercetin on the natural killer (NK-92) cells proliferation: a potential role as immunomodulatory - Aung Myo Oo@Mohd Hasym; Nasir Mat Nor; Liyana Hazwani Mohd Adnan; Nor Zidah Ahmad; Septama, Abdi Wira; Nik Nurul Najihah; Ohn, Mar Lwin; Nordin Simbak (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cancer can be classified as a fourth leading cause of death in Malaysia. There is a continuous effort by scientists in finding alternative cure to cancer due to the known side effects of chemotherapy and radiation therapy as well as recurrences. One of the latest methods to kill cancerous cells is by using immune cells known as natural killer (NK) cells. Flavonoids such as flavone and flavonol are also known for their antioxidant, anti-inflammatory, immunomodulatory and anticancer properties. This study was carried out to determine the role of flavonoid compounds of apigenin, luteolin, and quercetin to facilitate the growth of NK-92 cells. NK-92 cell line was grown in tissue culture flasks containing α- Minimum Essential Medium (MEM) medium enriched with L-glutamine, 12.5% fetal bovine serum, 12.5% horse serum, 0.2 mM myo-inositol, 0.02 mM folic acid, and 100 - 200 U/mL recombinant interleukin 2 (IL-2). The cell viability was determined via trypan blue staining where the cells were manually counted by a haemocytometer. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to determine the cell viability of NK-92 cells after treatment with apigenin, luteolin, and quercetin. Results showed a dose-dependent proliferative effects of apigenin, luteolin, and quercetin on the proliferation of NK-92 cells showing the highest percentage of proliferation at 100 µg/mL for all compounds (*P < 0.05). However, exceeding the dose of 100 µg/mL had resulted in a decline of cell proliferations percentage. Based on these findings, flavonoid compounds comprising apigenin, luteolin and quercetin were able to induce proliferative effects on NK-92 cells.